A (in)sustentabilidade em pequenas propriedades rurais: o caso de seis municípios localizados no extremo oeste paranaense - Engel, Werner (2012)
The objective of this research was to analyse and to identify the agricultural sector in the cities established in the far west of Paraná State, focusing on small farms, determinants factors of sustainability and the perspectives for the future of these properties. Data collection was conducted through questionnaires, interviews that sought to highlight the characteristics of the farmer and his production unit and data about how the producer view his property, and how he perceives this perspectives for the future. The data were the basis of the analysis in the verification of financial, economic, social and environmental (un)sustainability, noting the presence or not of the small landowner in his activities. With the outcome of this case study, it contributes to the knowledge of this portion of the population and the authorities can direct resources and policies to encourage production and income to reduce the rural exodus because it was found unsustainable trends of small farms in the cities studied.